Corrigendum: The fabrication of a gellan gum-based hydrogel loaded with magnesium ions for the synergistic promotion of skin wound healing - Li, Wenqiang; Jian, Xingling; Zou, Yanfen; Wu, Lin; Huang, Haiyan; Li, Hui; Hu, Dandan; Yu, Bo (Frontiers in Bioengineering and Biotechnology, 2023)
Graphical Abstract